Incorporating Diversity in Marketing Education: A Framework for Including All People in the Teaching and Learning Process. (April 2020) - Rivera, Reynaldo G.; Arrese, Angel; Sádaba, Charo; Casado, Luis
The management of diversity and inclusion is a major challenge for businesses in developing inclusive products and marketing strategies focused on people with disabilities. Universities can foster positive attitudes toward inclusiveness if they facilitate student recognition of differences as assets and enable them to appreciate the creation of communities where different individuals are valued. This study analyzes the experience of an innovative undergraduate seminar on inclusive marketing based on social learning theory. Designed and conducted by a former marketing manager with visual impairment, together with university scholars, the course develops the learning potential of inclusive marketing strategies and tactics through role-playing exercises and case studies. By presenting the inclusive marketing seminar theoretical framework, syllabus, and impact on students' attitudes, this research analyzes an approach to training future marketing professionals and leaders to understand people with disabilities as important stakeholders and provides key insights for universities, companies, and governments in the application of inclusive marketing and communication strategies.